2008
DOI: 10.1152/ajpcell.00227.2007
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation capacity of the renal proximal tubule involves the bulk of differentiated epithelial cells

Abstract: We investigated the proliferative capacity of renal proximal tubular cells in healthy rats. Previously, we observed that tubular cells originate from differentiated cells. We now found 1) by application of bromo-deoxyuridine (BrdU) for 14 days and costaining for BrdU, and the G 1-phase marker cyclin D1 that the bulk of cells in the S3 segment of juvenile rats were involved in proliferation; 2) that although the proliferation rate was about 10-fold higher in juvenile rats compared with adult rats, roughly 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
125
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 28 publications
10
125
1
2
Order By: Relevance
“…In early descriptive studies, it has been proposed that regeneration of proximal tubular cells occurred from any surviving tubular cell following mild to moderate injury (5)(6)(7). In addition, stainings for cyclin D1, Ki-67, and BrdU suggested that fully differentiated tubular cells were either growth arrested or had progressed to the G1 phase, potentially acting as a reserve to rapidly reenter the cell cycle upon injury (6).…”
mentioning
confidence: 99%
“…In early descriptive studies, it has been proposed that regeneration of proximal tubular cells occurred from any surviving tubular cell following mild to moderate injury (5)(6)(7). In addition, stainings for cyclin D1, Ki-67, and BrdU suggested that fully differentiated tubular cells were either growth arrested or had progressed to the G1 phase, potentially acting as a reserve to rapidly reenter the cell cycle upon injury (6).…”
mentioning
confidence: 99%
“…23 What is uncontested is the increase in mitotic activity within damaged tubules. 24 It has also been suggested that cells within the proximal tubule rest in G 1 rather than G 0 , potentially priming them for a rapid proliferative response to injury. 24 Despite these data, more recently, several other possibilities have been proposed including (1) recruitment of stem cells from distant sites in the body (e.g., bone marrow), (2) the presence of a persistent stem/progenitor within the postnatal renal epithelium and/or (3) the recruitment of a stem/progenitor population from a non-epithelial compartment of the kidney.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…24 It has also been suggested that cells within the proximal tubule rest in G 1 rather than G 0 , potentially priming them for a rapid proliferative response to injury. 24 Despite these data, more recently, several other possibilities have been proposed including (1) recruitment of stem cells from distant sites in the body (e.g., bone marrow), (2) the presence of a persistent stem/progenitor within the postnatal renal epithelium and/or (3) the recruitment of a stem/progenitor population from a non-epithelial compartment of the kidney. We will not discuss the literature pertaining to the recruitment of bone marrow cells to the kidney in response to injury here other than to reference that it has been extensively studied, and while this can occur, the evidence would suggest that integration of such cells into the renal parenchyma is very rare, with the repair process largely involving cell populations within the kidney itself.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The rationale for this is that there is a large reserve of these cells in the G 1 phase that enables them to elicit a proliferative response when activated. [31][32][33] More recently, it has been reported that the repair of renal proximal tubules is facilitated by self-duplication of differentiated epithelial cells and not by intra-tubular progenitor cells, as previously suggested. This same study also reports that the cells most likely to be involved in the repair process are the result of dedifferentiation/redifferentiation events.…”
mentioning
confidence: 98%